Analysis of risk factors of rapid thyroidal radioiodine-131 turnover in Graves’ disease patients - Ruiguo Zhang (Nature Portfolio, 2017)
Abstract Rapid iodine-131(131I) turnover in the thyroid gland is an important feature of Graves’ disease (GD) and also a strong predictor of radioiodine therapy failure. The aim of this study was to explore the predictors of rapid 131I turnover. The clinical data on 2543 patients were retrospectively reviewed. Patients were divided into 2 groups depending on present or absent with rapid 131I turnover defined as a 4-hour to 24-hour 131I uptake ratio of ≥1. Overall, 590 cases (23.2%) had a rapid 131I turnover. In the univariate analysis, gender, age, FT3/FT4 concentration, disease duration, with or without antithyroid drugs (ATD), time of ATD, thyroid weight and thyroid textures displayed significant differences. Cutoff values of age, FT3 and thyroid weight to predict rapid 131I turnover were 38 years, 35 pmol/l and 56 g by receiver operating characteristic curves. Binary logistic regression analysis further revealed higher probability of rapid 131I turnover in patients with thyroid weight ≥56 g (odds ratio [OR]:3.7, 95% confidence interval [CI]: 3.032–4.559), age <38 years (OR:2.3, 95%CI: 1.906–2.856), FT3 concentration ≥35 pmol/l (OR:7.6, 95%CI: 5.857–8.563) and females (OR:2.2, 95%CI: 1.757–2.791). In conclusion, larger goiters, younger age, higher FT3 concentration and females are independently associated with rapid 131I turnover in GD patients.